The nuances of transformation: a study on the rural society of Bangladesh - Amreen, Adiba; Khan, Ahmed; Priom, Atiqur Rahman; Ahmad, Amarraah; Fouzder, Arnab; Mehzabeen, Iffat Sumaiya; Boishakhi, Kinnory; Khan, Masuma Warda; Chowdhury, Mahima; Ahmed, Ruhaima Ridita; Sharothi, Shakira; Samrin, Tahia (2024)
Despite its bustling urban centres in Dhaka and Chittagong, Bangladesh has a majority of its population living in the sprawling rural landscape- around 68% of the population is located in the country's rural areas. Although its contribution to the country's GDP is low, the majority of the people living in these areas are also involved in agricultural workfarming, keeping poultry and fish, etc. However, in the past few decades, there has been an increase in income diversifying in the rural areas, meaning that there are more and more different opportunities and types of work that people are turning to for income generation besides agriculture. This means that there are notable changes in not just the occupations, but also in the very social fabric of rural Bangladesh via changes in class relations and circumstances, marriage and religious affiliations, greater connectivity and literacy, and healthcare and educational opportunities. Many Government and non-government agencies are working in the field in these areas, however, there is a considerable gap in the research of rural society in its own nuanced context. That is the gap that this report aims to fill. The method adopted by this study is mainly qualitative. A group of 17 students from the Anthropology Program at BRAC University visited the villages of the Ishwarganj Union in Ishwarganj Upazila, Mymensingh, where the students were divided into groups each covering a different relevant topic to gain a holistic understanding of the condition of the villages. These groups conducted semi-structured interviews of random participants with their consent, each in the field of their topic, e.g. students studying the rural market went to the markets in the villages, while those studying the domestic units visited homes. The overarching theme of the study was transformation. The mental image of the rural areas of Bangladesh continues to be one of the traditional villages one may encounter in the media, however, with the globalisation and greater infrastructure and connectivity, that image is from a bygone era. This is the essence that the chapters of the study aim to capture, and it was revealed through participant observation and interviews how the villages of Bangladesh have considerably changed. The old systems of being mainly connected through one’s family and ethnicity have evolved to now having homes known for their prominent members’ occupations. The rural market and economy have greatly diversified and now most products are readily available for most in the markets. Education and healthcare have reached rural Bangladesh, which was once a struggle due to poor infrastructure and access. This has also allowed governance and law to reach the rural areas, which were previously governed by village courts or shalish. However, this means new challenges. Greater connectivity and globalisation have meant that new kinds of problems are entering these villages. Newfound competitiveness has made it difficult for old businessmen to keep up with demands, and farmers find themselves at the mercy of market syndicates which dictate their ability to sell their goods on the market. Many youths are facing drug addiction with the introduction of synthetic recreational drugs like Yaba through the borders. Public education and healthcare are still lacking and inefficient, leading to people having to find solutions elsewhere, such as opting for a religious education for their children instead of a secular government one, often leading to women and girls opting out of higher education entirely. Moreover, old problems continue to persist in the form of dowry and child marriages but manifest in new ways. Following the above, certain recommendations are made: (1) Rural Social Structure: More households should adopt a mixed approach to income generation to keep up with the diversifying economy. Besides this, more faith leaders should become involved in the discouragement of dowry and child marriage. (2) Rural Social Structure Contemporary Rural Economies: A more comprehensive economic strategy should be developed, involving government initiatives, grassroots measures and continuous research. Increased training and digital literacy should be implemented to aid the transition from a traditional economy to a globalised economy. (3) Rural Land Management: Sufficient knowledge about one's rights and inheritance is still unclear, thus improving basic legal literacy and addressing these gaps before taking policy measures to eradicate the key issue of land dispute. (4) Rural Politics: The moderation of and fair government intervention into contemporary capitalist change-making agents such as NGOs is necessary to ensure rural labour is not exploited. (5) Rural Governance and Law: The creation of an accountable and transparent Government body is necessary, which can adapt to cultural changes and enforce goal-based policies aiming for rural transformation and decentralising urban centres to fit the needs of the rural populace. (6) Rural Infrastructure: Digital capacity-building workshops would be an invaluable resource for both school teachers and medical practitioners. Providing incentives such as mid-day meals led to the children being able to pay better attention and having a significant improvement in their academic performance, creating economic incentives to create jobs but also to make sure that the future labour force has appropriate levels of education. The healthcare institution requires proper transparency and communication channels existing among the healthcare providers and officials. Easier transfer processes of doctors and other staffers, and better logistical support (to avoid backlog) are important in healthcare institutions. (7) Impacts of Globalisation on Rural Bangladesh: Institutional efforts such as access to medical aid and rehabilitation may help early-stage youth fight narcotics addictions. Alongside this, widespread awareness programs for parents and youth should be held.